Physical examinations for older adults with shoulder pain: a narrative review - Sangwoo Kang; Suk-Woong Kang (The Ewha Medical Journal)
Shoulder pain is a common complaint in primary care settings. The prevalence of shoulder pain is on the rise, especially in societies with aging populations. Like other joint-related conditions, shoulder pain is predominantly caused by degenerative diseases. These degenerative changes typically affect bones, tendons, and cartilage, with common conditions including degenerative rotator cuff tears, impingement syndrome, and osteoarthritis. Diagnosing these degenerative diseases in older adults requires a thorough understanding of basic anatomy, general physical examination techniques, and specific diagnostic tests. This review aims to outline the fundamental physical examination methods for diagnosing shoulder pain in older adult patients in primary care. The shoulder's complex anatomy and its broad range of motion underscore the need for a systematic approach to evaluation. Routine inspection and palpation can identify signs such as muscle atrophy, bony protrusions, or indications of degenerative changes. Assessing range of motion, and distinguishing between active and passive deficits, is crucial for differentiating conditions like frozen shoulder from rotator cuff tears. Targeted strength tests, such as the empty can, external rotation lag, liftoff, and belly press tests, are instrumental in isolating specific rotator cuff muscles. Additionally, impingement tests, including Neer’s and Hawkins’ signs, are useful for detecting subacromial impingement. A comprehensive understanding of shoulder anatomy and a systematic physical examination are vital for accurately diagnosing shoulder pain in older adults. When properly executed and interpreted in the clinical context, these maneuvers help differentiate between various conditions, ranging from degenerative changes to rotator cuff pathology.